Pengaruh Pendidikan Kesehatan tentang Toilet Training pada Anak Toddler Berdasarkan the American Academy of Pediatrics Guide Terhadap Self-Efficacy pada Caregiver di Puspa Daycare - Kurnia Meishinta Dewi; Windy Rakhmawati; Ai Mardhiyah (Universitas Malahayati, 2024)
ABSTRACT Diaper dermatitis is a condition that children are prone to. The prevalence of diaper dermatitis tends to decrease when children stop using diapers and receive toilet training. Toilet training is a developmental task that must be achieved by toddlers, if it is not achieved, it will have an impact on the child’s physiology and psychology, such as urinary track infection, feelings of inferiority, and maladaptive socialization. The inisiation of toilet training in children is carried out by the caregiver, especially mother at home, but the current phenomenon is that many parents work so children are left in daycare. So, in the condition of children in daycare, the inisiation of toilet training in children is carried out either by the mother who entrusts her child to daycare or by the caregiver at the daycare. The success of toilet training is influenced by caregiver self-efficacy which can be improved through health education about toilet training for children based on effective guidelines. This study aims to analyze the effect of health education about toilet training for toddlers based on The American Academy of Pediatrics Guide on caregiver self-efficacy in Puspa Daycare. This research used a quasi experimental design with one group pre-test and post-test. Sampling used total sampling, obtained 33 participants. The self-efficacy instrument was adapted from the General Self-Efficacy Scale (GSES). Data analysis used the Wilcoxon test. The results of the analysis showed that there is a significant difference between self-efficacy before and after providing health education (p =0,000). The conclusion of this research is that health education about toilet training for toddlers based on The American Academy of Pediatrcs Guide had an effect on increased the self-efficacy of caregivers at Puspa Daycare. This health education can be an intervention for pediatric nurses in provided nursing services to caregivers regarding toilet training for toddler in daycare. Keywords: Caregiver, Daycare, Health Education, Self-Efficacy, The American Academy of Pediatrics Guide ABSTRAK Diaper dermatitis merupakan kondisi yang rentan terjadi pada anak. Prevalensi diaper dermatitis cenderung berkurang saat anak berhenti menggunakan diapers dan mendapatkan toilet training. Toilet training merupakan tugas perkembangan yang harus dicapai oleh anak toddler, jika tidak dicapai maka akan berdampak pada fisiologis hingga psikologis anak, seperti infeksi saluran kemih, perasaan rendah diri, dan sosialisasi tidak adaptif. Inisiasi toilet training pada anak dilakukan oleh caregiver terutama orang tua di rumah, namun fenomena saat ini banyak orang tua bekerja sehingga anak dititipkan di daycare. Maka, pada kondisi anak di daycare, inisiasi toilet training pada anak toddler dilakukan baik oleh ibu yang menitipkan anaknya di daycare maupun oleh pengasuh di daycare. Keberhasilan toilet training dipengaruhi oleh self-efficacy pada caregiver yang dapat ditingkatkan melalui pendidikan kesehatan tentang toilet training pada anak toddler berdasarkan panduan yang efektif. Penelitian ini bertujuan untuk menganalisis pengaruh pendidikan kesehatan tentang toilet training pada anak toddler berdasarkan The American Academy of Pediatrics Guide terhadap self-efficacy pada caregiver di Puspa Daycare. Penelitian ini menggunakan desain quasi experimental dengan one group pre-test and post-test. Pengambilan sampel menggunakan total sampling, didapatkan 33 partisipan. Instrumen self-efficacy diadaptasi dari General Self-Efficacy Scale (GSES). Analisa data menggunakan uji Wilcoxon. Hasil analisis menunjukkan terdapat perbedaan yang signifikan antara self-efficacy sebelum dan sesudah pemberian pendidikan kesehatan (p = 0,000). Simpulan pada penelitian ini adalah pendidikan kesehatan tentang toilet training pada anak toddler berdasarkan The American Academy of Pediatrics Guide berpengaruh terhadap peningkatan self-efficacy pada caregiver di Puspa Daycare. Pendidikan kesehatan tentang toilet training ini dapat menjadi intervensi bagi perawat anak dalam memberikan pelayanan keperawatan kepada caregiver tentang toilet training pada anak toddler di daycare. Kata Kunci: Caregiver, Daycare, Pendidikan Kesehatan, Self-Efficacy, The American Academy of Pediatrics Guide